2016
DOI: 10.3390/e18120424
|View full text |Cite
|
Sign up to set email alerts
|

Measurement on the Complexity Entropy of Dynamic Game Models for Innovative Enterprises under Two Kinds of Government Subsidies

Abstract: Abstract:In this paper, setting the high-tech industry as the background, we build a dynamic duopoly game model in two cases with different government subsidies based on the innovation inputs and outputs, respectively. We analyze the equilibrium solution and stability conditions of the system, and study the dynamic evolution of the system under the conditions of different system parameters by the numerical simulation method. The simulation results show that both innovation subsidy policies have positive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Guo et al [14] investigated the effects of government R&D projects on firm’s innovation outputs. Similarly, Ma et al [15] found that the degree of government innovation subsidy showed an effect on the stability and entropy of the dynamic duopoly game model in two cases. Sabri et al [16] developed a framework capturing the dynamics changes between innovation implementation and allocation decisions.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Guo et al [14] investigated the effects of government R&D projects on firm’s innovation outputs. Similarly, Ma et al [15] found that the degree of government innovation subsidy showed an effect on the stability and entropy of the dynamic duopoly game model in two cases. Sabri et al [16] developed a framework capturing the dynamics changes between innovation implementation and allocation decisions.…”
Section: Literature Reviewmentioning
confidence: 93%
“…It should be noted that one of the methods in the existing studies is a combination of information entropy with various mathematical (statistical) methods, for example, with regression analysis [7] and the game theory [8]. Thus, the use of entropy offers a great opportunity compared to traditional approaches.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…where U is the total energy of an organization; ΔU is an increase in energy; A is labor; Q is the heat that is formed under the influence of T temperature and S energy entropy. The above are the basic categories of thermodynamics, which have quite definite content for such specific systems as organizations [8]:…”
Section: Formalization Of the Energy Entropy Of Organizationsmentioning
confidence: 99%
“…Jin et al [19] constructed two supply chain models, including manufacturers, consumers and governments, on the basis of which the optimal government subsidies and the optimal output and price of products were obtained through game theory and utility functions. Fan and Dong [20] explored and built an evolutionary game model including enterprises and consumers, discussed the choice of government subsidy strategies in low-carbon diffusion, and gave four kinds of government subsidy strategies.…”
Section: Literature Reviewmentioning
confidence: 99%